Protein and DNA synthesis demonstrated in cell-free Ehrlichia chaffeensis organisms in axenic medium - Vijay K. Eedunuri (Nature Portfolio, 2018)
Abstract Ehrlichia chaffeensis, a tick-transmitted rickettsial bacterium, is the causative agent of human monocytic ehrlichiosis. Biochemical characterization of this and other related Rickettsiales remains a major challenge, as they require a host cell for their replication. We investigated the use of an axenic medium for E. chaffeensis growth, assessed by protein and DNA synthesis, in the absence of a host cell. E. chaffeensis organisms harvested from in vitro cultures grown in a vertebrate cell line were fractionated into infectious dense-core cells (DC) and the non-infectious replicating form, known as reticulate cells (RC) by renografin density gradient centrifugation and incubated in the axenic medium containing amino acids, nucleotides, and different energy sources. Bacterial protein and DNA synthesis were observed in RCs in response to glucose-6-phosphate, although adenosine triphosphate, alpha-ketoglutarate or sodium acetate supported protein synthesis. The biosynthetic activity could not be detected in DCs in the axenic medium. While the data demonstrate de novo protein and DNA synthesis under axenic conditions for E. chaffeensis RCs, additional modifications are required in order to establish conditions that support bacterial replication, and transition to DCs.